Penerapan Model Regresi Logistik Ordinal pada klasifikasi status Gizi Baduta di Kabupaten Flores Timur - Agnes Ona Bliti Puka; Vinsensius Crispinus Lemba; Joko Purwadi (Universitas Ahmad Dahlan, 2022)
The problem of malnutrition is urgent in East Flores Regency. The purpose of this study was to determine the factors that influence the nutritional status of under-fives in East Flores Regency. This study used cross-sectional data with a sample of 400 children aged 12-59 months. The research data is secondary data obtained from the Social Assessment and Development Foundation. Nutritional status is measured by weight and age index. Nutritional status is classified into very short, short, and regular. The results showed a significant relationship between parenting and eating patterns, water and sanitation, government services and health services, and the nutritional status of under-fives. The role of community nurses is needed in education and empowerment to improve the nutritional quality of under-fives.